Pengaruh Metode Periodic Order Quantity (POQ) terhadap Tingkat Efisiensi Pengadaan Material Proyek di PT. Antero Makmur - Nita Sulistyowati; Euis Komalawati; I Nyoman Purnaya (Jurnal Logistik Indonesia, 2020)
Material costs. Some of the causes are the inaccurate estimation of the amount of material and erroneous delivery time plans. Both lead to a shortage or excess of material orders, and inefficient time of ordering. This research aims to determine the efficiency of the Periodic Order Quantity (POQ) method on the project material procurement of PT. Antero Makmur. The independent variable of this research is the Periodic Order Quantity (POQ) method and the dependent variable is the efficiency level of material procurement. This research uses a quantitative method with PT Antero Makmur’s employees who handle the procurement process directly as the population. Twenty people were sampled by using a non-probability sampling method, namely a saturated sample. The data collection instrument is the questionnaire and the data were processed with statistical analysis software SPSS version 25. The results showed that there was a significant positive effect from the application of the Periodic Order Quantity (POQ) method towards material procurement efficiency by 55.9% with an R² value of 0.559. Based on the result of the t count performed with the results of the analysis, the number of t count 4.772 is greater than the number of t table 2.1. In conclusion, the H0 is rejected and H1 is accepted, which means that the POQ method variable (X) has a significant effect on the material procurement efficiency level variable (Y).